Listeria monocytogenes cancer vaccines: bridging innate and adaptive immunity - Morrow, Zachary T. (Curr Clin Microbiol Rep, 2019)
PURPOSE OF THE REVIEW: Immunotherapy has emerged as a promising cancer treatment, however success in only select clinical indications underscores the need for novel approaches. Recently Listeria monocytogenes-based vaccines have been developed to drive tumor specific T-cell responses. Here, we discuss recent preclinical studies using L. monocytogenes vaccines, innate immune pathways that influence T-cell priming, and new vaccine strategies in clinical trials. RECENT FINDINGS: Recent studies indicate that in addition to inducing antigen specific T-cell responses, L. monocytogenes vaccines remodel the TME. In addition, several innate immune pathways influence adaptive immune responses to L. monocytogenes and modulating these pathways holds promise to enhance anti-tumor T-cell responses. SUMMARY: The interplay between innate and adaptive immune responses to L. monocytogenes is poorly understood. Understanding these interactions will facilitate the design of better anti-cancer vaccines and improved use of combination therapies.